PELATIHAN PEMBUATAN VIRGIN COCONUT OIL (VCO) BAGI SISWA SISWI SMK DAN SMA MUTIARA 17 AGUSTUS - Rizky Arcinthya Rachmania; Elly Wardani (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2019)
Adolescence is prone to deviations and impropriety should be grown a sense of creativity. Creativity of students to be skilled in making VCO so that will grow entrepreneurship spirit for students. Skills in the way of making VCO is expected to increase students' creativity and applied in economic activities to increase student income. The solution offered from the problems that have been mentioned above, then training the manufacture of Virgin Coconut Oil (VCO) is very necessary. Program activities offered in the form of socialization or introduction of VCO products produced both from the benefits and advantages they have compared with other similar products, and there is also a demonstration later in the making of VCO and explanation of how the right and proper marketing. Implementation of community service is specifically a promotive effort in the field of business development to create skilled and productive student students in producing a health product that can later be utilized both for themselves, the family and the surrounding community. Community service activities, also relevant to economics and business, where the product will be marketed so that this can be an income or additional income for local students. The participants' response to this counseling is quite high, indicated by the attendance rate of 80% of the number of invitations. Understanding high school students and SMK Mutiara to the benefits and content of VCO and how to manufacture the correct VCO using this simple and cheap enzymatic method was responded with great enthusiasm by the participants.